67 Improving efficiency of care for adult type 2 diabetic patients under secondary care. (12th November 2018) - Khan, Naveed; Alam, Faisel; Morjaria, Aaron; Walsh, Michael; Nathan, Yashica
Abstract : This quality improvement paper aimed to improve the efficiency of care for type 2 diabetes mellitus patients. This was done by analysing why patients are not being discharged from hospital diabetic care back to the community whilst creating a novel discharge criterion to help standardise the process. In England over 9% of the population have been diagnosed with diabetes; with £13 billion a year being spent on treatment. In the current financial climate, we must ensure that the vast resources being spent are spent as efficiently as possible. As medical students at the Lewisham and Greenwich trust we found a lack of a discharge criterion made it difficult to discharge patients from hospital care back to the community. Therefore, to improve quality of care and bring cost savings to the department, we aimed to define a clear discharge criterion to de-escalate patients to primary/community care, maintaining optimum care, and increasing the number of discharged patients by 10% over a 12 month period. We performed two PDSA cycles on 501 randomly selected patients and found an extra 11.27% of patients could be de-escalated down to community care (from secondary) using our criteria. This quality improvement project could optimise and improve quality of care for diabetic patients in the appropriate setting. Diabetes care is estimated to account for at least 5% of UK total healthcare expenditure, and up to 10% of NHS expenditure. Specifically, each outpatient appointment costs on average £115., thus reducing inappropriate patient loads provides considerable cost savings for the trust. This model could be translated across to other departments and other trusts to optimise and improve the quality of care for many thousands of patients.